Mechanisms of disease: macrophage-derived foam cells emerging as therapeutic targets in atherosclerosis. - Choudhury, R; Lee, J; Greaves, D (2005)
The limited efficacy of current treatment strategies for targeting atherosclerosis and its complications requires new therapeutic options to be explored. From early fatty-streak lesions to advanced plaques, macrophage-derived foam cells are integral to the development and progression of atherosclerosis. Elucidation of molecular and cellular processes involving macrophages has led to numerous therapeutic targets being suggested. Potential sites of intervention range from monocyte recruitment, through cholesterol uptake and esterification, to cholesterol evacuation and macrophage egress from plaque. In addition, complex patterns of transcriptional regulation of genes involved in macrophage lipid homeostasis and in the regulation of inflammation have been partly unraveled. Recognition of ATP-binding cassette cholesterol transport mechanisms and cellular interactions with cholesterol-accepting apolipoproteins (or synthetic mimetics) opens up new potential therapies to induce atherosclerosis regression in humans. This review presents a systematic evaluation of actual and potential macrophage-directed pharmacologic interventions. It reflects the timely convergence of three important strands: advances in molecular and cell biology that have suggested therapeutic targets in macrophages; the development of multiple classes of drugs targeting these pathways; and the emergence of sensitive imaging techniques that have enabled identification of changes in plaque size and composition in response to treatment.